The Effect Of Manual Therapy On Myofascial Trigger Point Syndrome Upper Trapezius - Wiyono Putra, Yosa Endrika; Santoso, Totok Budi (UNIB Press, 2024)
MTP's in the Upper Trapezius muscle is a condition where there is a pain point along the trapezius muscle which contains a collection of symptoms and complaints due to spasm or shortening of the trapezius muscle which is often felt as a stiff neck or nape, various manual therapy modalities are expected to be able to overcome this complaint. This study uses a quantitative approach with non-parametric test statistics. This study is a quasi-experimental case study with a treatment group without a control group with 10 research subjects who experienced MTP's in the Upper Trapezius muscle given manual therapy actions consisting of C0-C1; C2-C6; C7-T1 traction and stretching the upper Trapezius muscle, Friction sub occipitalis muscle. The parameters observed were pain in motion and joint range of motion. The action was given 3 times for two weeks, respondents will be examined before and after the 3rd therapy. There was a decrease in pain and LGS after manual therapy intervention was given with a significance value (p 0.001) in the influence test using the Willcoxon Test. From the results of this study, it was found that there is an influence of manual therapy on the MTP's Upper Trapezius muscle which can reduce patient symptoms and complaints.